2015
DOI: 10.1097/ta.0000000000000579
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury without radiologic abnormality in children

Abstract: Systematic review, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 15 publications
2
18
1
5
Order By: Relevance
“…9 The neuroimaging findings are classified into MRI patterns. 1 In 43% of patients, no abnormalities were detectable by MRI (Type I), while 57% had abnormal scan results (Type II). Of these, 6% had extra neural abnormalities alone (Type IIa), while 38% showed isolated intraneural lesions (Type IIb).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…9 The neuroimaging findings are classified into MRI patterns. 1 In 43% of patients, no abnormalities were detectable by MRI (Type I), while 57% had abnormal scan results (Type II). Of these, 6% had extra neural abnormalities alone (Type IIa), while 38% showed isolated intraneural lesions (Type IIb).…”
Section: Discussionmentioning
confidence: 98%
“…Spinal cord injury (SCI) in children is a challenging condition for the treating surgeon and paediatrician. 1 It is considered to be rare, with an estimated incidence of 4.6per million children per year. 2 Spinal cord injuries without radiologic abnormality (SCIWORA) were first described by Pang & Wilberger 3,4 in 1982.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we were unable to investigate the frequency of cervical central spinal cord injury patterns among patients with SCIWORA. 12,13 In case reports, Jung et al 14 reported a 7-year-old boy who complained of weakness in both arms (but not his lower extremities) after completing a standing high jump. This case showed no evidence of bone abnormalities on computed tomography of the cervical spine, but MRI revealed observable swelling with increased signal intensity at the C1-C4 levels.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 To further improve the interpretability and comparability of MRI findings in patients with a clinicoradiological mismatch, an MRI-based classification system has been introduced. 4,6 The present study aimed (1) to further characterise the clinical features of adult patients presenting with SCIWORA, (2) to apply the MRI classifications system in a consecutive cohort and (3) to assess its prognostic value in the prediction of the early neurological outcome in this population.…”
Section: Introductionmentioning
confidence: 99%